Interactions between microbial community structure and pathogen survival in soil - Moynihan, Emma Louise (Cranfield University, 2012)
Manure and slurry are valuable resources that may enhance many soil properties. However, organic amendments can pose a significant health risk to both humans and livestock if not managed correctly due to pathogenic loads that may be carried within them. Therefore it is crucial to identify the factors that affect pathogen survival in soil, in order to gain maximum benefit from such resources, whilst minimising the threat to public and animal welfare. This research aimed to elucidate the impact of microbial community structure on pathogen decline following entry to such organisms into the soil. It was hypothesised that pathogen survival would be significantly influenced by both diversity and phenotypic configuration of the microbial community. This was experimentally investigated within three distinctly different biological contexts. Cont/d.